Experimental study of road deicing by using the urban groundwater under the climatic condition of Nuremberg city, Germany - Baumgärtel, Sebastian; Rohn, Joachim; Luo, Jin (SN Applied Sciences, 2020)
Traffic accidents caused by heavy icing and snowing kept increasing in Germany in recent years, and many deicing methods were therefore developed. These methods either harm the environment (deicing salt) or damage roads (snowplows). As an alternative, the heating of roads using electricity or heated water has been proposed. This study considers the direct use of groundwater for road deicing in urban centers. The climatic and hydrological setting of Nuremberg city is referenced for a testing setup inside a cooling chamber using concrete slabs to test inlet water temperatures under different ambient temperatures. They were designed with 100 mm and 200 mm coil distance and both with an installation depth of around 40 mm. Additionally, an outside test field in a similar fashion is built to validate the measurements inside a chamber. The experiments indicated that a groundwater temperature of 10 degrees C is sufficient to keep the surface ice-free in typical winter days in the study area. Furthermore, the snow did not accumulate on the outside test field during snowfall events. The usability of this heating method could, therefore, be recommended for road deicing under such climatic condition.
CRIS-Team WoS Importer:2020-06-16